Routine Activity Theory and Farm Equipment Theft: A Macro-Level Approach - Osborne, Dustin L.; Swartz, Kristin (International Journal of Rural Criminology, 2021)
Though a handful of studies have explored the relationship between farm characteristics and theft of farm equipment, all have been focused at the micro level. Put differently, they have sought to determine whether a relationship exists between likelihood of theft victimization and the characteristics (e.g., size, location) of individual farming operations. The current study builds upon this work by seeking to determine whether county-level factors (in line with the routine activity theory framework) serve to influence the incidence of farm equipment theft within counties. Data are derived from the National Incident-Based Reporting System, the Census of Agriculture and the United States Census of the Population.  Results are on the whole supportive of the theory's application to the problem and suggest that macro-level investigations constitute a worthwhile approach to better understanding agricultural victimization.